High‐Resolution and Facile Patterning of Silver Nanowire Electrodes by Solvent‐Free Photolithographic Technique Using UV‐Curable Pressure Sensitive Adhesive Film. Issue 12 (15th October 2021) - Yoo, Dongwoo; Won, Dong‐Joon; Cho, Woosung; Kim, Seonghyeon; Kim, Joonwon
Abstract: Patterning of silver nanowires (AgNWs) used in fabricating flexible and transparent electrodes (FTEs) is essential for constructing a variety of optoelectronic devices. However, patterning AgNW electrodes using a simple, inexpensive, high‐resolution, designable, and scalable process remains a challenge. Therefore, herein a novel solvent‐free photolithographic technique using a UV‐curable pressure sensitive adhesive (PSA) film for patterning AgNWs is introduced. The UV‐curable PSA film can be selectively patterned by photopolymerization under UV exposure through a photomask. The AgNWs embedded in the non‐photocured adhesive areas of the film are firmly held by a crosslinked network of photocurable resin when the patterned film is attached to the AgNW‐coated substrate and additionally irradiated by UV light. After peeling off the film, the positive pattern of AgNW electrodes remains on the substrate, while the negative pattern is transferred to the film. This solvent‐free photolithographic technique, which does not use toxic solvents, provides superior pattern features, such as fine line widths and spacings, sharp line edges, and low roughness. Therefore, the developed technique could be successfully applied in the development of flexible and transparent optoelectronic devices, such as a self‐cleaning electro‐wetting‐on‐dielectric (EWOD) devices, transparent heaters, and FTEs. Abstract : The proposed solvent‐free photolithographic technique for patterning silver nanowires uses an ultraviolet‐curable pressure sensitive adhesive film. This photolithographic technique does not use toxic solvents, is an eco‐friendly, upscalable, simple, and cost‐efficient fabrication method, and produces high‐quality patterns with a fine line width and spacing, sharp line edges, and low roughness. This technology could facilitate the development of flexible and transparent optoelectronics.